1994
DOI: 10.1177/088626094009002003
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism and Elder Abuse

Abstract: A comparison group study of abusing and nonabusing caregivers suggested a correlation between alcohol use and abuse and violence against elderly parents. Findings reveal that abusers were more likely than nonabusers to drink, to become intoxicated, and to be identified as having a drinking problem. Policy and practice implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 8 publications
3
37
0
4
Order By: Relevance
“…In contrast, the characteristics of victims are most relevant for financial abuse (Anetzberger, Korbin, & Austin, 1994;Podnieks, 1992).…”
Section: Downloaded By [Adams State University] At 12:32 21 November mentioning
confidence: 95%
“…In contrast, the characteristics of victims are most relevant for financial abuse (Anetzberger, Korbin, & Austin, 1994;Podnieks, 1992).…”
Section: Downloaded By [Adams State University] At 12:32 21 November mentioning
confidence: 95%
“…62 Tatara's study of abuse across 18 states also found that family members were the suspected abusers in two-thirds of the cases. 63 Various characteristics of the abusing individual that have been found to be associated with abuse of an elder in a home setting, include advanced age, 64 alcoholism, 65 intellectual de cits, 66 inadequate communication skills, 67 substance abuse, 68 depression, 69 poor physical health, 70 stress, 71 social isolation, 72 nancial dif culties, 73 and dependence on the elderly individual. 74 Individuals also may be more likely to abuse the elder if they are limited in their understandin g of the elder's physical and emotional needs 75 or if they have LOUE unrealistic expectations about the elder's abilities or the likelihood of a favorable prognosis.…”
Section: Risk Factors For Elder Abuse and Neglectmentioning
confidence: 98%
“…Evidence of either mental health problems or alcohol misuse on the part of the abuser were noted in four of the six case control studies considered (Anetzberger et al 1994;Bristowe and Collins 1989;Homer and Gilleard 1990;Phillips 1983Phillips , 1986Pillemer 1986). …”
Section: Intra-individual Dynamicsmentioning
confidence: 95%
“…The studies were undertaken by the following researchers: Anetzberger et al (1994), Bristowe and Collins (1989), Grafstrom et al (1992), Homer and Gilleard (1990), Phillips (1983;, Pillemer (1986). Two of the studies were from Europe (Grafstrom et al 1992;Homer and Gilleard 1990) …”
Section: Risk Factorsmentioning
confidence: 99%